Characterization of the glucosylated anthocyanin profile of 27 red grape (Vitis vinifera L.) varieties grown in Portugal: insights for climate change adaptation - Baltazar, Miguel; Monteiro, Eliana; Pereira, Sandra; Carvalho, Márcia; Correia, Elisete; Ferreira, Helena; Silva, Vânia; Valente, Joana; Alves, Fernando; Castro, Isaura; Gonçalves, Berta (Frontiers in Plant Science, 2026)
IntroductionClimate change poses significant challenges to viticulture, increasing the need for sustainable adaptation strategies such as the identification of resilient Vitis vinifera L. varieties.MethodsThis study characterized the anthocyanin content, profile, and color parameters of 27 red grape varieties cultivated under the same terroir in the Douro Demarcated Region over two consecutive years. Berry biochemical analyses, including chromatographic and colorimetric techniques, alongside gene expression of the anthocyanin biosynthesis genes MybA1, UFGT, and OMT, were conducted to assess varietal and annual variability.ResultsTotal anthocyanin content varied significantly among varieties, ranging from 0.14 mg malvidin-3-O-glucoside equivalents per g of dry weight (mg M3G·g-1 DW) in ‘Bastardo’ to 8.63 mg M3G·g-1 DW in ‘Vinhão’. While most varieties demonstrated increased anthocyanin content in the warmer and drier 2022 season, such as ‘Tinto Cão’ and ‘Touriga Franca’; a few displayed notable declines, notably ‘Vinhão’, highlighting differential responses to abiotic stress. Anthocyanin profiles were dominated by malvidin derivatives, which correlated with enhanced color stability. Nonetheless, cyanidin-3-O-glucoside increased in 2022 in some varieties, while delphinidin and petunidin-3-O-glucosides decreased. CIELAB parameters indicated darker and higher color saturation in berries in 2022, being associated with increases in total anthocyanin content and malvidin derived compounds. Gene expression analysis of MybA1, UFGT, and OMT in six varieties revealed different behaviors.DiscussionAmong all varieties under study, stable anthocyanin profiles across years were observed which could suggest increased resilience potential. These findings highlight the interplay between genetic and environmental factors in shaping anthocyanin dynamics, supporting the use of varietal selection as an adaptation strategy to optimize quality, resilience, and sustainability in wine regions under climate change.